Impact of Pharmacist Involvement on the Utility of a Gram-Negative Blood Culture Identification Panel on Antimicrobial Usage. (December 2021) - Bowman, Caitlin; Holloway, Melissa; Scott, Lisa; Russell, Carmen; Lott, Sonia; Amin, Raid
Background: A rapid molecular diagnostic test (MDT) is a test used to identify several different species of gram-negative bacteria and their genetic resistance markers. However, the impact of rapid MDT has not been established when combined with pharmacist involvement.Objective: To determine the impact of pharmacy involvement on patient outcomes when using rapid MDT. The primary outcome is the time from gram stain result to the first dose of the targeted antibiotic.Methods: This is a single-center, quasi-experimental, 1-group pretest-posttest design study of patients with gram-negative bacteremia in a community hospital. Hospitalized patients 18 years or older were included if they had a gram-negative blood culture. Patients were excluded if they were discharged or expired prior to culture results. Outcomes were compared between patients prior to and after implementation of the automated MDT. This research was determined to be exempt from institutional review board oversight consistent with West Florida Healthcare and in accordance with institutional policy.Results: The use of rapid MDT combined with pharmacist intervention resulted in a statistically significant decrease in the time to targeted antibiotic therapy (pre-intervention group, n = 77, 44.8 ± 17.8 hours versus post-intervention group, n= 80, 4.4 ± 5.8 hours; P ≤.001). There was no significant difference found between secondary outcomes. Limitations included small sample size as well as inconsistent documentation.Conclusions: The use of rapid MDT combined with pharmacist intervention resulted in a statistically significant decrease in the time to targeted antibiotic therapy.